Variasi Perekat Tar Sengon, Tar Mahoni Dan Tar Sekam Padi Terhadap Karakteristik Pembakaran Briket Kokas Lokal Terkarbonasi - Wibowo, Hirdiyanto, Ir. Subroto, MT, Ir. Sartono Putro, MT (2015)
This study aimed to compare the effective ignition and combustion characteristics resulting from the type of adhesive Grajen sengon tar , tar and tar Grajen mahon rice husk. The initial process by including coke briquettes in an electric furnace whose temperature can be controlled up to a temperature of 9000 C , where the sample is placed in a container briquettes that are in the middle of the electric furnace , and heated to temperatures of up to burn out. Data is collected every 1 minutes until constant mass , the recorded data is the temperature coke briquettes and coke briquettes mass reduction . The results showed variations in the type of adhesive greatly affect the temperature of combustion , flame effectively produced . A briquette using tar Grajen Falcata combustion temperatures are a high of 8600 in the 86th minute , effective flame for 90 minutes . Briquettes USING mahogany Grajen tar contained the highest combustion temperature of 8260C in the 83rd minute , effective flame for 84 minutes . USING tar rice husk briquettes are the highest combustion temperature of 8510C in the 77th minute , effective flame for 79 minutes .